2014
DOI: 10.5888/pcd11.130327
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exposure to Secondhand Smoke Among Vietnamese Adults: California Vietnamese Adult Tobacco Use Survey, 2007–2008

Abstract: Because smoking rates are high among Vietnamese men, we used data from the 2007–2008 California Vietnamese Adult Tobacco Use Survey to estimate secondhand smoke exposure and associated risk factors among Vietnamese nonsmokers. Thirty percent of nonsmokers were exposed to secondhand smoke (SHS) at home, 8% at work, 52% in bars, and 67% on a college campus. At home, odds of SHS exposure were greater for women than for men and for adults aged less than 40 years than for older adults. Odds of SHS exposure were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Smoking behavior is a cultural norm in some communities, such as among men in Southeast Asian countries, and smoking prevalence remains high among males in those race/ethnic groups in the U.S. [40]. A study of non-smoking Vietnamese adults in California found high secondhand exposure in home environments for women [41]. Social dynamics may play a role; a study of family communication in Vietnamese and Chinese families identified a pattern of “suffering in silence [42].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking behavior is a cultural norm in some communities, such as among men in Southeast Asian countries, and smoking prevalence remains high among males in those race/ethnic groups in the U.S. [40]. A study of non-smoking Vietnamese adults in California found high secondhand exposure in home environments for women [41]. Social dynamics may play a role; a study of family communication in Vietnamese and Chinese families identified a pattern of “suffering in silence [42].…”
Section: Discussionmentioning
confidence: 99%
“…The topic of infant and adolescent tobacco smoke exposure has also been investigated (12)(13)(14)(15). Studies that make no distinction based on age are also relatively available (16)(17)(18)(19), but there are very few adult-focused studies (20). Some studies have also addressed women's exposure to tobacco smoke (21-25).…”
Section: Introductionmentioning
confidence: 99%
“…13 These include communities of Bangladeshi and Pakistani origin, in which rates of smoking among men are higher than those in the general population. 13 As living with a smoker is an important determinant of SHS exposure, 14 , 15 these groups are likely to have higher levels of exposure than the general population. The extent of SHS exposure among minority ethnic groups in the United Kingdom has not been quantified; however, we found that in areas predominantly populated by South-Asian populations, smoking took place regularly in front of children in 42% of households with smokers.…”
Section: Introductionmentioning
confidence: 99%